Latin Lesson Lectio Aulae - Paço, Eliana (Richtmann Publishing, 2012)
Latin language in Albania is a rare language studied and confined just at the Faculty of Medicine, Faculty of Historyand Philology (Department of Albanian language and Literature and Department of History), Faculty of Foreign Languages.Several researchers and linguists, such as I. Zamputi, P. Gjeci, K. Cipo, R. Andoni, H. Subashi, K. Qiriazati, E. Paço and N.Basha have undertaken serious attempts at designing the programs on Latin language teaching targeted at students of theFaculties due to the needs that Latin learning poses in this domain. The texts have been designed in terms of the theoretical andpractical aspects, students’ needs and in line with a better acquisition of the other courses related to Latin and Old Greeklanguages learning. This article will lay an emphasis on the different methods of Latin teaching, aspects of an accuratetranslatability of the medical terminology and some suggestions related to different kinds of exercises used at school aiming at abetter acquisition of the courses related and dependent on Latin learning incorporated at the Faculty of Medicine.